2019
DOI: 10.1523/jneurosci.0696-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Sound-Sensitive Source of Alpha Oscillations in Human Non-Primary Auditory Cortex

Abstract: The functional organization of human auditory cortex can be probed by characterizing responses to various classes of sound at different anatomical locations. Along with histological studies this approach has revealed a primary field in posteromedial Heschl's gyrus (HG) with pronounced induced high-frequency (70–150 Hz) activity and short-latency responses that phase-lock to rapid transient sounds. Low-frequency neural oscillations are also relevant to stimulus processing and information flow, however, their di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 99 publications
(139 reference statements)
11
44
2
Order By: Relevance
“…In agreement with the view of co-existing mechanisms for target enhancement and distractor suppression (Houghton & Tipper, 1984), a presumably facilitatory effect of low alpha power was observed in regions directly involved in the processing of auditory information (see also Billig et al, 2019), while a potentially suppressive effect of high alpha power was present in motor and frontal regions. What follows from this is that anatomically separate alpha oscillators implement different cognitive functions.…”
Section: Functional Specification Requires Anatomical Separationsupporting
confidence: 85%
“…In agreement with the view of co-existing mechanisms for target enhancement and distractor suppression (Houghton & Tipper, 1984), a presumably facilitatory effect of low alpha power was observed in regions directly involved in the processing of auditory information (see also Billig et al, 2019), while a potentially suppressive effect of high alpha power was present in motor and frontal regions. What follows from this is that anatomically separate alpha oscillators implement different cognitive functions.…”
Section: Functional Specification Requires Anatomical Separationsupporting
confidence: 85%
“…Non-primary auditory cortex in HGal and STG did not show the same delta power increase as HGpm; indeed power in these regions was more suppressed across low-frequencies (delta-alpha). This distinction between oscillatory signatures in primary and non-primary auditory fields is similar to that observed during active listening to speech (Billig, et al, 2019). In our previous fMRI study (Kumar, et al, 2016), we showed a greater increase in BOLD signal (compared to primary auditory cortex) as we moved up the hierarchy to lateral HG and planum temporale.…”
Section: Delay Activity In Higher-order Lateral Temporal Cortexsupporting
confidence: 84%
“…S11). Though there are different sensory alphas in the cortex, our work complements other findings which find broadly similar alpha physiology across areas (39,68,69). However, careful work will need to be done to tease apart how alpha varies between regions.…”
Section: Discussionsupporting
confidence: 63%